Mircea cel Batran, a Symbol of the Dobrogean Consciousness - Kaiter, Edith-Hilde; Moise, Ioan Gabriel (Technium Sustainability, 2021)
As the historical sources inform us, Mircea cel Batran had an extremely important influence in Dobrogea, being the ruler who managed to unite Dobrogea and Wallachia. While the Ottoman Empire was kept at a distance, the Romanian Voivode, as a good administrator and strategist, fortified Dobrogean fortresses and cities such as Isaccea, Enisala, Caliacra and Silistra. The discoveries of monetary treasures, consisting of coins dating from the time of Mircea cel Batran, spread throughout Dobrogea, prove the prosperity of the province during the time of the great Voivode, achieved through the intense trade of goods that took place and the important role the Romanian currency played in trade. Youtube link: https://www.youtube.com/watch?v=Q3qSAvswC0E